2013
DOI: 10.1007/s00595-013-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of surgery in lung cancer patients with schizophrenia

Abstract: The postoperative morbidity and long-term results of schizophrenic patients with lung cancer were acceptable. Therefore, even in patients with schizophrenia, surgical treatment for lung cancer should be recommended when deemed to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…38 Other studies similarly found that patients with a major mental illness are less likely to receive chemotherapy, radiation, or surgery for colon cancer 64 and are less likely to have surgery for oral cancer. 130 Individuals with schizophrenia are less likely to receive stageappropriate treatment for lung cancer, 127 surgery for esophageal cancer, 61 and referrals to clinical trials. 61 There are a few exceptions to this pattern of treatment disparities, most notably for chemotherapy rates among breast cancer patients with schizophrenia.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Other studies similarly found that patients with a major mental illness are less likely to receive chemotherapy, radiation, or surgery for colon cancer 64 and are less likely to have surgery for oral cancer. 130 Individuals with schizophrenia are less likely to receive stageappropriate treatment for lung cancer, 127 surgery for esophageal cancer, 61 and referrals to clinical trials. 61 There are a few exceptions to this pattern of treatment disparities, most notably for chemotherapy rates among breast cancer patients with schizophrenia.…”
Section: Treatmentmentioning
confidence: 99%
“…61 Increased prevalence of health risk behaviors and comorbidities, such as chronic obstructive pulmonary disease, obesity, diabetes, and cardiovascular disease, can complicate treatment and contribute to poorer outcomes. 38,44,127 Fragmented primary, oncology, and mental health services 129 ; providers' stigmatizing beliefs or behaviors 128 ; and "diagnostic overshadowing"when clinicians misattribute physical symptoms to a mental illness rather than, correctly, to a physical illness-may also delay appropriate diagnosis and treatment, especially for individuals with schizophrenia and other SMI. 44,61 Once diagnosed, patients often face perceptions that they are "difficult patients" who lack the capacity to make treatment decisions or adhere to treatment regimens or may become violent.…”
Section: Treatmentmentioning
confidence: 99%
“…Concern regarding violence in individuals with schizophrenia may also influence oncology care. One case series describing surgical care for patients with lung cancer and schizophrenia emphasized the importance of restricting surgical candidates to patients with schizophrenia who are at low risk for agitation . At the systems level, patients are often treated for schizophrenia in mental health clinics that are physically separate from general hospitals and use different electronic records.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenic patients are impaired in their biological response to stress, so it is important to take careful consideration when evaluating such patients for surgical interventions, especially in cardiac surgery (2). We aimed to present an acute paranoid schizophrenic patient with huge left atrial myxoma treated with robotic techniques.…”
Section: Introductionmentioning
confidence: 98%